Mudik Assistance Application Using Android-Based Scrum Method - Ardhana, Muhammad Reza; Alda, Muhamad (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Homecoming is an activity undertaken by nomads and migrant workers to return to their hometowns. In Indonesia, going home is synonymous with annual traditions starting from religious and national holidays such as Eid al-Fitr, Eid al-Adha, Christmas and New Year. However, going home is often accompanied by traffic jams and confusion, which can be a nuisance for travelers. Therefore, a possible solution to overcome this problem is to develop a mobile application to support homecoming. This research focuses on developing an Android-based homecoming assistance application using the Scrum methodology. The aim is to create technological solutions that make it easier for Indonesian people to return home every year. The development process is divided into sprints, and each sprint lasts two weeks. Each sprint includes planning, developing, and evaluating features such as real-time maps, traffic information, stop locations, and emergency response systems. The development team works closely with stakeholders to ensure that the application meets user needs. The research results show that the use of the Scrum methodology increases development efficiency and improves the quality of the final product. The resulting application prototype received a positive response in user testing. 90% of participants found the app useful when returning home. In conclusion, the development of homecoming assistance applications using the Scrum methodology has produced an effective and user-friendly solution to help travelers. This research opens up opportunities for further development and large-scale implementation in the future.